دور تنظير البطن في تشخيص بعض حالات العقم - الدالي, عصام; صالح, حسن; هزيم, خلود (مجلة جامعة تشرين للبحوث والدراسات العلمية- سلسلة العلوم الصحية, 2019)
أجريت الدراسة في مشفى الأسد الجامعي باللاذقية في قسم التوليد وأمراض النساء خلال عامي 2007 ـ 2008 وتضمنت الدراسة ( 105 ) مريضات يعانين من العقم لمدة سنة أو أكثر، اجري لهن تنظير بطن تشخيصي. تم تقسيم المريضات لمجموعتين ( 70 ) مريضة عقم بدئي و( 35 ) مريضة عقم ثانوي أجري لهن تنظير بطن استقصائي لعدة استطبابات مباشرة شملت الشك بآفة بوقية 32.3%,الصورة الظليلة للرحم والبوقين غير طبيعية 24.76 %,عقم مجهول السبب 20% ,مبيض متعدد الكيسات 17.1%, الشك بأندومتريوز 3.8%, كيسة مبيض 1.9%, بلغت الإيجابية الكاذبة والسلبية الكاذبة للصورة الظليلة 15%,18.3% على التوالي. This study was done in the Department of Obstetrics and Gynecology at Al-Assad University Hospital in Lattakia during the year 2007 – 2008. It included (105) patients who suffered from infertility for one year or more, and they underwent diagnostic laparoscopy. We divided the patients into two groups: Group I: (70) patients with primary infertility. Group II: (35) patients with secondary infertility. The indications were as follows: 1. The suspicion with tubal lesion 32.3%. 2. Abnormal hysterosalpingography (HSG) 24.76%. 3. Unexplained infertility 20%. 4. Polycystic ovary (pco) 17.1%. 5. Endometriosis 3.8%. 6. Ovarian cyste 1.9%. The false positive value and false negative value of (HSG) was 15%, 18.3% respectively.